2013
DOI: 10.1186/2047-2994-2-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of universal screening on MRSA bacteremias in a single acute NHS organisation (2006–12): interrupted time-series analysis

Abstract: BackgroundIn November 2004, a national target was set for the English hospital trusts to reduce the Meticillin-Resistant Staphylococcus aureus (MRSA) bacteremia rate by 60% by April 2008 against the number during 2003/04 (baseline year). In our organisation the number of MRSA bacteremias had risen since 2002 and peaked at 75 in 2005/06. A target was set to reduce the number and series of specific and non- specific interventions was introduced including universal MRSA screening. This study analyzes the impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Although the majority of isolates were staphylococci and streptococci species as in other studies, a falling number of isolated Staphylococcus aureus strains and an increase in Gram‐negative species, predominantly E. coli and Klebsiella pneumonia , in the absence of a change in anaerobic species have been demonstrated. These data may reflect the effectiveness of anti‐MRSA interventions across UK hospitals, which coincides with the study period [30, 31]. However, this pattern was also seen in patients presenting as an emergency from the community.…”
Section: Discussionmentioning
confidence: 69%
“…Although the majority of isolates were staphylococci and streptococci species as in other studies, a falling number of isolated Staphylococcus aureus strains and an increase in Gram‐negative species, predominantly E. coli and Klebsiella pneumonia , in the absence of a change in anaerobic species have been demonstrated. These data may reflect the effectiveness of anti‐MRSA interventions across UK hospitals, which coincides with the study period [30, 31]. However, this pattern was also seen in patients presenting as an emergency from the community.…”
Section: Discussionmentioning
confidence: 69%
“…During the animal experimental period, the chickens in the NC8-ChIL17B + IBV group displayed obvious improvements in growth compared to the NC8-P+IBV group. Although it is common sense that the probiotic effect of L. plantarum promotes growth performance by changing the microbial balance of the intestinal flora, the expression of cytokines such as IL-2, IL-4, IL-6 IFN-γ, and IL-22, which participate in the cytokine–endocrine hormone interaction network, affect the growth of epithelial cells in the digestive tract, improving digestion and metabolism [ 39 , 40 ]. Similar results were observed in our previous study, in that the fusion cytokine IL-4/6 promoted the growth performance of piglets [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological surveillance of bacterial infection and resistance to antibiotics are essential for awareness creation, implementation of control measures and effective management of infections. This is important in developing countries particularly in sub-Saharan Africa where studies have indicated that many hospitals have rudimentary and poor enforcement of infection control measures and marginal awareness on the extent of infections caused by multi-drug resistant bacteria which have resulted in increased morbidity and mortality [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%